Proceedings Particle Accelerator Conference
DOI: 10.1109/pac.1995.504719
|View full text |Cite
|
Sign up to set email alerts
|

Low emittance lattice for LEP

Abstract: In order to obtain the largest luminosity with LEP2, it is attractive to make the beam emittance as small as possible because the beam-beam effect is not a limitation at the energy of E 90 GeV for the obtained bunch currents. This can be achieved with a high tune lattice. Two possible candidates are lattices with a horizontal phase advance of 108 0 or 135 0 per cell. Both have a vertical phase advance of 60 0 . These lattices were developed during 1994 and the results are presented. Tests to reach high intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…All the nonlinear elements (sextupoles) are in the arc cells. Low-emittance lattices have been envisaged for LEP as a mean to increase the luminosity at low current [1]. In one of these lattices, which was found to be difficult to operate, the arc FODO cells have an horizontal phase advance of 135 and a vertical phase advance of 60 .…”
Section: Experience With a Strong Focusing Latticementioning
confidence: 99%
See 1 more Smart Citation
“…All the nonlinear elements (sextupoles) are in the arc cells. Low-emittance lattices have been envisaged for LEP as a mean to increase the luminosity at low current [1]. In one of these lattices, which was found to be difficult to operate, the arc FODO cells have an horizontal phase advance of 135 and a vertical phase advance of 60 .…”
Section: Experience With a Strong Focusing Latticementioning
confidence: 99%
“…This led us to an extensive analysis of the problems associated with this lattice in order to understand why it was so difficult. A report on this study is available [2] and some of the results concerning this lattice can be found at this conference [1]. One interesting outcome of this study was that it is not possible to correct both third order resonances and horizontal anharmonicity.…”
Section: Experience With a Strong Focusing Latticementioning
confidence: 99%